2022
DOI: 10.5662/wjm.v12.i4.305
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human leishmaniasis in Sudan: A systematic review and meta-analysis

Abstract: BACKGROUND There are three main forms of leishmaniasis in humans: cutaneous leishmaniasis (CL), visceral leishmaniasis (VL), and mucocutaneous leishmaniasis. The prevalence of human leishmaniasis varies widely in different countries and different regions of the same country. To date, there is no overall estimation of the prevalence of human leishmaniasis in Sudan. AIM To determine the pooled prevalence of human leishmaniasis and the disease risk factors among Sudanese c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
0
11
1
Order By: Relevance
“…and dogs in the southern part of Gadarif State, eastern Sudan, was higher than the country-wide prevalence[6], likely due to the combination of environmental and socioeconomic factors. Gadarif State is a known endemic area for Leishmania, with favorable ecological conditions for the transmission of the parasite.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…and dogs in the southern part of Gadarif State, eastern Sudan, was higher than the country-wide prevalence[6], likely due to the combination of environmental and socioeconomic factors. Gadarif State is a known endemic area for Leishmania, with favorable ecological conditions for the transmission of the parasite.…”
mentioning
confidence: 76%
“…The disease can manifest in different forms, such as cutaneous (CL), visceral (VL), mucocutaneous (MCL), or postkala-azar dermal leishmaniasis (PKDL), depending on the parasite species and the host immune response. Leishmaniasis is endemic in many regions of Sudan, with CL being the most common form and VL being mainly confined to the eastern, western, and southern parts of the country [4][5][6]. Leishmaniasis affects 98 countries in Europe, Africa, Asia, and America, with a high burden in 13 countries that account for over 90% of new cases [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This high prevalence aligns with findings from studies conducted in other parts of Sudan and East Africa, where environmental conditions and socio-economic factors contribute to higher rates of infection. A recent systematic review by [10] in Sudan revealed that the overall pooled prevalence of human leishmaniasis in the country is 21%. Cutaneous leishmaniasis (CL) is the most common type, with a prevalence of 26%, followed by visceral leishmaniasis (VL) at 18%.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of many past studies have shown that males are highly affected by VL compared to females in different endemic areas of the world such as in Sudan [36][37][38], in Ethiopia [29,31,39], in Indian subcontinent [40], and in Brazil [33]. The males to females ratio is 60% versus 40% in Sudan [36], 77% versus 23% in Kenya [41], and 76% versus 24% in India [42], 87% versus 13% in Ethiopia [43]. To explain this disparity between the sexes, two hypotheses were proposed.…”
Section: Contribution Of This Workmentioning
confidence: 99%
“…However, several studies have been done to provide an insight into efficient control mechanisms. The findings of many past studies have shown that males are highly affected by VL compared to females in different endemic areas of the world such as in Sudan [ 36 38 ], in Ethiopia [ 29 , 31 , 39 ], in Indian subcontinent [ 40 ], and in Brazil [ 33 ]. The males to females ratio is 60% versus 40% in Sudan [ 36 ], 77% versus 23% in Kenya [ 41 ], and 76% versus 24% in India [ 42 ], 87% versus 13% in Ethiopia [ 43 ].…”
Section: Introductionmentioning
confidence: 99%